Analysis of Land Use Changes Along the Coast of Sidoarjo Regency Due to Rob Floods - Dhahlan, Muhammad; Sudarko, Niken Ayu Rahma; Sukananda, Satria (Marcapada: Jurnal Kebijakan Pertanahan, 2022)
Sedati Subdistrict is an area that has the largest mangrove forest along the east coast of Sidoarjo Regency. This mangrove forest serves to withstand the waves and prevent the abrasion of sea waves around the coastal area. Unfortunately, some mangroves have suffered damage due to land conversions that triggered rob flood. This study aims to determine and explain the physical conditions before and after rob flood, land use changes, and mangrove growth along the coast of Sidoarjo. This study employed the qualitative method and adopted the image interpretation approach. The satellite image used is Google Earth, showing a high-resolution Geo Eye satellite image (0.41 meters) in panchromatic mode and (1.65 meters) in spectral mode taken in 2015, 2017, 2018, 2019, and 2021. The authors interpreted the image using a digital method by digitizing and classifying the land use on a scale of 1:20,000. The observation object is the area affected by rob flood. The results indicated that before and after rob flood, there were changes in land use along the coast. Most of the locations affected by flooding are overgrown with mangroves. In addition, sedimentation occurs in those locations because the water carries sand which accumulates to the land so that it forms a channelbar. The authors concluded that there have been changes in land use in the last five years along the coast of Sedati Subdistrict. In 2015, the coastal region was still visible, but in 2017, it disappeared due to the loss of mangroves which caused abrasion. The change in the shoreline occurred very significantly, especially in 2019, which was due to the impact of rob flood.